Cloning and Expression of GST-HMPREF0351_11084 Gene in JM105 Cells: A New Potential Protein Vaccine for Pneumococcal - Sddiq Ghani Al-Muhanna (Journal of Global Pharma Technology, 2018)
The HMPREF0351_11084 gene encoding pneumococcal vaccine antigen A family protein (GeneID: 12999770) was optimized and synthesized, then sub-cloned into pGH cloning vector. The amplified HMPREF0351_11084 gene was incorporated into Bam HI and Eco RI sites of pGEX-2T GST expression vector under the control of tac promoter. The recombinant pGEX-2T was transformed and expressed into JM105 cells. The protein of expressing bacteria was analyzed by SDS-PAGE and the target protein was detected by Western blot - enhanced chemiluminescence (WB-ECL) assay. The result shows predicted target fusion protein with molecular weight 51.2 kDa. The current study describes for the first time the expression of HMPREF0351_11084 gene, and so attempts to produce a new potential protein vaccine for pneumococcal. Further extensive study is required to generate more data about HMPREF0351_11084 protein and evaluate its immunization in elicits antibodies that are capable of passively protecting against pneumococcal infections.Keywords: Fusion protein, PGEX-2T, HMPREF0351_11084, ECL, Pneumococcal vaccine.